Analytic Framework to Determine Proximity in Relationship Coffee Models. Issue 2 (17th November 2019) - Edelmann, Hanna; Quiñones‐Ruiz, Xiomara Fernanda; Penker, Marianne
Abstract: In conventional food systems, there are often large social and geographical distances between production and consumption. Alternative food networks (AFNs) like relationship coffee models aim to shorten these distances through direct contacts, communication, trust, transparency or commitment to improve farmers' livelihoods. These relationship coffee models appear in diverse shapes with various implications for producers. Therefore, we deductively develop a framework to conceptualise proximity in four dimensions (organisational, institutional, cognitive and social) with subdimensions and three transversal dimensions ((temporary) geographical proximity, power, and communication). The analytic framework is complemented by an illustrative case to empirically test it, showing high geographical,  organisational, institutional and cognitive proximity but low social proximity between coffee producer and restaurant owner. For future research, the framework can help to conceptualise proximity or to distinguish different types of relationship coffee models and to unpack conditions under which relationship coffees can increase proximity between coffee producers and buyers, often located far apart.